# Tan(3x)(tanx-1)=0

## Simple and best practice solution for Tan(3x)(tanx-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Tan(3x)(tanx-1)=0 equation:

Simplifying
Tan(3x)(tanx + -1) = 0
Remove parenthesis around (3x)
anT * 3x(tanx + -1) = 0
Reorder the terms:
anT * 3x(-1 + antx) = 0
Reorder the terms for easier multiplication:
3anT * x(-1 + antx) = 0
Multiply anT * x
3anxT(-1 + antx) = 0
(-1 * 3anxT + antx * 3anxT) = 0
(-3anxT + 3a2n2tx2T) = 0
Solving
-3anxT + 3a2n2tx2T = 0
Solving for variable 'a'.
Factor out the Greatest Common Factor (GCF), '3anxT'.
3anxT(-1 + antx) = 0
Ignore the factor 3.
Subproblem 1Set the factor 'anxT' equal to zero and attempt to solve:
Simplifying
anxT = 0
Solving
anxT = 0
Move all terms containing a to the left, all other terms to the right.
Simplifying
anxT = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1 + antx)' equal to zero and attempt to solve:
Simplifying
-1 + antx = 0
Solving
-1 + antx = 0
Move all terms containing a to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + antx = 0 + 1
Combine like terms: -1 + 1 = 0
0 + antx = 0 + 1
antx = 0 + 1
Combine like terms: 0 + 1 = 1
antx = 1
Divide each side by 'ntx'.
a = n-1t-1x-1
Simplifying
a = n-1t-1x-1Solutiona = {n-1t-1x-1}`